2017 ESC FOCUSED UPDATE ON DUAL ANTIPLATELET THERAPY IN CORONARY ARTERY DISEASE DEVELOPED IN COLLABORATION WITH EACTS - article editorial (Российский кардиологический журнал, 2018)
The Task Force for dual antiplatelet therapy in coronary artery disease of the European Society of Cardiology (ESC)and of the European Association for Cardio-Thoracic Surgery(EACTS)